2021
DOI: 10.1002/adbi.202000220
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Electronic Properties of Metal Oxide Nanoparticles to Reveal Their Toxicity Mechanism and Safe‐by‐Design Approach

Abstract: Metal oxide (MO) nanoparticles (NPs) are widely applied to medicine, agriculture, industry, and other fields, however, their potential toxicity is often concerned. Various toxicological studies are carried out to investigate the toxicity and underlying mechanism of MO NPs. A series of physicochemical properties of MO NPs, such as primary size, charge, solubility, crystal structure, crystalline phase, etc., are correlated with their induced toxicity. Recently, electronic properties of MO NPs have exhibited inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 67 publications
0
3
0
Order By: Relevance
“…The remaining uncertainty surrounding nanomedicine is partially caused by insufficient efforts spent in studying fundamental structure–activity relationships (SARs). ,,, Contemporary research has identified that the physicochemical properties of a NP, such as size, shape, composition, surface properties, and crystal structure/phase, ultimately control its biological fate, chemical reactivity, and toxicity. A recent meta-analysis by Labouta et al found that NP cytotoxicity could be primarily predicted from the material’s chemistry, followed by NP concentration, size, cell type, and the cytotoxicity screening indicators . Other factors, such as surface charge and redox potentials, are also valuable parameters, although they are often insufficiently reported. Labouta et al ’s meta-analysis, for example, observed that 64% and 56% of the representative publications lacked appropriate reporting of surface chemistry and zeta-potential (surface charge), respectively . Other reviews have also noted that a lack of consideration of NP transformations in the biological environment can result in incorrect identification of the relevant characteristics. , When investigating NP size effects, the formation of an adsorbed protein layer on the NP surface is often not accounted for, leading to incorrect assumptions about the NP’s in vivo size and behavior.…”
Section: Current Challenges and Gaps For Regulators And Researchersmentioning
confidence: 99%
“…The remaining uncertainty surrounding nanomedicine is partially caused by insufficient efforts spent in studying fundamental structure–activity relationships (SARs). ,,, Contemporary research has identified that the physicochemical properties of a NP, such as size, shape, composition, surface properties, and crystal structure/phase, ultimately control its biological fate, chemical reactivity, and toxicity. A recent meta-analysis by Labouta et al found that NP cytotoxicity could be primarily predicted from the material’s chemistry, followed by NP concentration, size, cell type, and the cytotoxicity screening indicators . Other factors, such as surface charge and redox potentials, are also valuable parameters, although they are often insufficiently reported. Labouta et al ’s meta-analysis, for example, observed that 64% and 56% of the representative publications lacked appropriate reporting of surface chemistry and zeta-potential (surface charge), respectively . Other reviews have also noted that a lack of consideration of NP transformations in the biological environment can result in incorrect identification of the relevant characteristics. , When investigating NP size effects, the formation of an adsorbed protein layer on the NP surface is often not accounted for, leading to incorrect assumptions about the NP’s in vivo size and behavior.…”
Section: Current Challenges and Gaps For Regulators And Researchersmentioning
confidence: 99%
“…The influence of band gap and band edge potential of metal oxides was studied to predict the nature of oxidative stress and pulmonary inflammation. It was observed that the metal oxide particles that were completely soluble in the biological environment and having a band gap value comparable to the cellular redox potential (-4.12 to -4.84 eV) induced high levels of toxicity [130]. Auffan et al [133] evaluated the influence of the redox state of iron-based nanoparticles and their cytotoxicity on strains of Escherichia coli.…”
Section: Metal Oxidesmentioning
confidence: 99%
“…Copyright 2013 The Royal Society of Chemistry). (E) Electron transfer behaviors in p -type and n -type MO NPs relative to BRPR of biological systems (Reprinted with permission from ref . Copyright 2021 Wiley-VCH).…”
Section: Electronic Band Structure-modulated Biosafety Of Nmsmentioning
confidence: 99%